2020
DOI: 10.1186/s12876-020-01333-9
|View full text |Cite
|
Sign up to set email alerts
|

Risk of rebleeding from gastroesophageal varices after initial treatment with cyanoacrylate; a systematic review and pooled analysis

Abstract: Background: Cyanoacrylate alone or in combination with other interventions, can be used to achieve variable rates of success in preventing rebleeding. Our study aims to assess the pooled risk of gastric and esophageal varices rebleeding after an initial treatment with cyanoacrylate alone and/or in combination with other treatments, by a systematic review of the literature and pooled analysis. Methods: PubMed, EMBASE, SCOPUS, and the Cochrane library were searched for studies that reported the risk of rebleedin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 51 publications
(32 reference statements)
0
15
0
Order By: Relevance
“…Several systematic reviews/meta-analyses have evaluated the efficacy of cyanoacrylate injection for the treatment of GVH [105][106][107][108][109] also significantly better in preventing the recurrence of gastric varices (36.0 % vs. 66.0 %; P = 0.002). There was no difference in AEs or mortality between the two groups.…”
Section: Initial Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Several systematic reviews/meta-analyses have evaluated the efficacy of cyanoacrylate injection for the treatment of GVH [105][106][107][108][109] also significantly better in preventing the recurrence of gastric varices (36.0 % vs. 66.0 %; P = 0.002). There was no difference in AEs or mortality between the two groups.…”
Section: Initial Managementmentioning
confidence: 99%
“…Two more recent systematic reviews/meta-analyses have reported similar results. Hu et al, after correcting for study heterogeneity, reported that, when gastric varices were treated with cyanoacrylate alone (n = 309), the risk of rebleeding was 15 % (95 %CI 11 % to 18 %) [108]. Chirapongsathorn et al included seven RCTs (n = 583) comparing endoscopic injection of N-butyl-2-cyanoacrylate glue with any other treatment approach not involving cyanoacrylate (propranolol only, EBL, or sclerotherapy with alcohol or ethanolamine).…”
Section: Initial Managementmentioning
confidence: 99%
“…Cyanoacrylate is a liquid substance which polymerizes and hardens rapidly when in contact with blood and produces a solid mass. Because the solid mass can induce vascular obliteration or strongly compress bleeding vessels, endoscopic intravascular or perivascular cyanoacrylate injection is widely used to treat esophageal and gastric varices, which can effectively stop and prevent variceal bleeding 20,21 . Cyanoacrylate is also often used to occlude the major feeding artery to ulcers as embolic agent to treat bleeding peptic ulcers on doing angiographic intervention therapy 22 .…”
Section: Discussionmentioning
confidence: 99%
“…Esophageal varices result from portal hypertension as a frequent manifestation of liver cirrhosis 1. About 60% to 80% of liver cirrhosis patients develop gastrointestinal varices 2,3. The frequency of developing esophageal varices is firmly attributed to the severity of the liver disease.…”
mentioning
confidence: 99%
“…BL or rubber-BL represents one of the oldest techniques in treating gastrointestinal varices 8. It is inferior to cyanoacrylate injection and embolization coils, regarding the overall success rate and rebleeding risk 3. However, BL is cost-effective, less technically demanding than the techniques mentioned above.…”
mentioning
confidence: 99%